An evaluation of the journal and audio-visual collections of the College of Science Library - Yabes, Mildred S. (School of Library and Information Studies, University of the Philippines Diliman, 2011)
This study was conducted to find out the particular forms of periodical and audiovisual materials preferred by the College of Science (CS) faculty and students; the periodical titles most often used; and the periodical and audiovisual titles needed by the faculty and students. This also sought to determine the usefulness of information derived from the periodical collection of the College of Science Library; know the difficulties and problems encountered by the library users in using the periodical collection; and determine if the College of Science Library's periodical and AV collections are adequate in supporting the information need of the CS faculty and students.